A decade of work on water governance at the OECD: what have we learnt?. Issue 2 (3rd March 2020) - Gurría, Angel
ABSTRACT: Our societies, economic systems and collective well-being depend on water security and access to water services. Yet, megatrends related to climate change, urbanization and demography are likely to generate more uncertainty about water availability and demand. Responding to these threats will require sharp actions to ensure universal access to drinking water and sanitation. Simultaneous action is also needed to invest in infrastructure and better articulate who does what, how, at which scale, and why. This article explores a decade of work on water governance at the OECD, providing key observations and lessons learnt.